2007
DOI: 10.1128/mcb.00931-06
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of the Adipocyte-Specific Secretory Protein Adiponectin Critically Depends on Thiol-Mediated Protein Retention

Abstract: Adiponectin is a secretory protein abundantly secreted from adipocytes. It assembles into a number of different higher-order complexes. Adipocytes maintain tight control over circulating plasma levels, suggesting the existence of a complex, highly regulated biosynthetic pathway. However, the critical mediators of adiponectin maturation within the secretory pathway have not been elucidated. Previously, we found that a significant portion of de novo-synthesized adiponectin is not secreted and retained in adipocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
283
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(297 citation statements)
references
References 48 publications
10
283
2
2
Order By: Relevance
“…Because PPAR␥ also increases HO-1 protein levels (21) and HO-1 is known as a chaperone protein, it is possible that one of the mechanisms by which HO-1 can increase adiponectin levels is through more efficient adiponectin stabilization and protection. This would confirm the report of Wang et al (47) that showed that the chaperone protein EroL increased adiponectin. We also have previously shown that upregulation of HO-1 protein in diabetic rats provided both cardio-protection and vascular protection against ROS (24).…”
Section: Decreasing Osupporting
confidence: 82%
See 1 more Smart Citation
“…Because PPAR␥ also increases HO-1 protein levels (21) and HO-1 is known as a chaperone protein, it is possible that one of the mechanisms by which HO-1 can increase adiponectin levels is through more efficient adiponectin stabilization and protection. This would confirm the report of Wang et al (47) that showed that the chaperone protein EroL increased adiponectin. We also have previously shown that upregulation of HO-1 protein in diabetic rats provided both cardio-protection and vascular protection against ROS (24).…”
Section: Decreasing Osupporting
confidence: 82%
“…PPAR␥ agonists are shown to induce both HO-1 (21) and the rate-limiting chaperone protein EroL (46,47). PPAR␥ agonist that increases adiponectin may do so by increasing the levels of EroL chaperone protein (46).…”
Section: Decreasing Omentioning
confidence: 99%
“…Several proteins have recently been shown to regulate adiponectin trafficking and secretion (27)(28)(29). However, the mechanisms regulating adiponectin multimerization and secretion remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, leptin does not appear to colocalize within Golgi (3), and Roh et al (67) suggested that, at least in adipocytes from young rats, separate leptin storage vesicles may exist. Like adiponectin (84), the endoplasmic reticulum (ER) may be a critical site for regulating leptin folding (it has one disulfide bond) and secretion. Future studies in which the expression or binding activity of potential chaperones is manipulated might help to explain the cellular trafficking of leptin with variations in nutritional or physiological status.…”
Section: Regulation Of Leptin Release At Posttranslational Stepsmentioning
confidence: 99%